PEMODELAN DAN PERAMALAN VOLATILITAS PADA RETURN SAHAM BANK BUKOPIN MENGGUNAKAN MODEL ASYMMETRIC POWER AUTOREGRESSIVE CONDITIONAL HETEROSKEDASTICITY (APARCH) - Nur Musrifah Rohmaningsih; Sudarno Sudarno; Diah Safitri (Jurnal Gaussian, 2016)
Stock is a sign of ownership of an individual or entity within a corporation or limited liability company. While the stock price index is a reflection of the movement of the stock price. Stock investments can not avoid the risk, so we need a model that can predict stock returns and volatility. Models are often used is ARCH/GARCH models. On the stock market also shows asymmetric effect(leverage), which is a negative relationship between the change in the value of returns with volatility movement. So, the model can be used is Asymmetric Power Autoregressive Conditional Heteroscedasticity (APARCH) model. APARCH model chosen to modeling and forecasting the volatility of Bukopin return stock is APARCH (1,2) model Keywords: Stock, volatility, asymmetric, return, APARCH